2012
DOI: 10.1071/an11366
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of epididymal spermatozoa from bull and red deer, stored at different times and temperatures before freezing - thawing

Abstract: In order to preserve male germoplasm, the recovery and cryopreservation of spermatozoa from the epididymides of hunted animals represents an accessible source of gametes. As a first experimental model, epididymal spermatozoa from slaughtered bulls were recovered at 30, 54, 78 and 102 h after death. The scrotal contents were stored at either 5 or 20°C. The sperm cells of each treatment (time + temperature combinations) were frozen with Triladyl (T) or Triladyl + Trehalose (TT) diluents. In order to assess sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Sperm harvested from the tail of epididymis differ from ejaculated spermatozoa in motility, membrane integrity, and DNA integrity [ 6 , 7 ], but they retain their fertilizing capacity [ 1 , 8 ]. Epididymal spermatozoa can be stored in both liquid and frozen state [ 9 , 10 ] before they are used for insemination [ 8 , 11 ]. Cervid spermatozoa are usually frozen in liquid nitrogen with the use of various extenders.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm harvested from the tail of epididymis differ from ejaculated spermatozoa in motility, membrane integrity, and DNA integrity [ 6 , 7 ], but they retain their fertilizing capacity [ 1 , 8 ]. Epididymal spermatozoa can be stored in both liquid and frozen state [ 9 , 10 ] before they are used for insemination [ 8 , 11 ]. Cervid spermatozoa are usually frozen in liquid nitrogen with the use of various extenders.…”
Section: Introductionmentioning
confidence: 99%
“…Time elapsed between the death and the samples recovery was about 7 days. Sperm cells were diluted in a Tris-glycerol-egg yolk extender, loaded in 0.25 mL straws, and frozen and stored in liquid nitrogen (Malcotti et al 2012). At thawing, sperm motility (SM), plasma membrane functionality (HOST), plasma membrane fluidity (M540), cell viability (CFDA), live cells with intact acrosome (LCIC), mitochondrial activity (MA), DNA integrity (DNA), area of sperm head (ASH), length of sperm head (LSH), width of sperm head (WSH) and ellipticity of sperm head (ESH) were assessed.…”
Section: Morphology and Physiology Evaluation Of Frozen-thawed Epidid...mentioning
confidence: 99%
“…Previous studies have shown that the sperm of many animal species, including mice [ 12 ], rams [ 13 ], dogs [ 14 ], and bulls [ 15 , 16 , 17 ], is resistant to low storage temperatures in the range of 0–6 °C. Iberian red deer spermatozoa can be stored in the epididymides for up to several days at a temperature 4–5 °C [ 7 , 18 ] before cryopreservation [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%